Altruism in world religions - Neusner, Jacob, 1932-; Chilton, Bruce (Washington, D.C. : Georgetown University Press, 2005)
"Exploring a range of philosophical and religious thought from Greco-Roman philia to the canonical statements of Judaism, Christianity, and Islam, from Hinduism in India to Buddhism and the religions of China and Japan, contributors to this volume probe the concept of altruism - unrewarded action for the sake of another person - to determine if it is a category that serves to advance the study of religion."--BOOK JACKET.
Introduction : altruism and the study of religion / William Scott Green -- 1. Altruism in Greco-Roman philosophy / Robert M. Berchman -- 2. Altruism in classical Judaism / Jacob Neusner and Alan J. Avery-Peck -- 3. Altruism in Christianity / Bruce Chilton -- 4. Altruism in Islam / Th. Emil Homerin -- 5. Altruism in classical Buddhism / Todd Lewis -- 6. Altruism in contemporary Buddhism : Thich Nhat Hanh's socially engaged Buddhism / Bradley S. Clough -- 7. Altruism in Japanese religions : the case of Nichiren Buddhism / Ruben L. F. Habito -- 8. Altruism in classical Hinduism / Richard H. Davis -- 9. Altruism in Chinese religions / Mark Csikszentmihalyi -- Epilogue / William Scott Green.
Includes bibliographical references and index.
Keywords: Altruism; Conduct of life; Religions